Expression analysis of phosphoenolpyruvate carboxykinase in Porphyra haitanensis (Rhodophyta) sporophytes and gametophytes. Issue 3 (21st May 2013) - He, Linwen; Zhang, Xiaojuan; Wang, Guangce
Summary: Phosphoenolpyruvate carboxykinase (PEPCK) catalyzes carboxylation of phosphoenolpyruvate or decarboxylation of oxaloacetate, which plays an important role in some C4 plants and algae. The full‐length cDNA of the PEPCK gene cloned from Porphyra haitanensis T. J. Chang et B. F. Zheng (Bangiales, Rhodophyta), was denoted Phpepck . It had a nucleotide sequence of 2300 bp, including a 5′‐untranslated region (UTR) of 147 bp, a 3′‐UTR of 329 bp and an open reading frame of 1824 bp. The expression of PEPCK in P. haitanensis sporophytes and gametophytes was examined at the levels of transcription, translation and enzyme activity. Both PEPCK abundance and activity were higher in sporophytes than those in gametophytes, suggesting that a C4 ‐like carbon‐fixation mechanism might be functional in P. haitanensis sporophytes.